1973
DOI: 10.1128/aem.26.1.18-21.1973
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds Produced in Sterile Fish Muscle (Sebastes melanops) by Pseudomonas putrefaciens, Pseudomonas fluorescens, and an Achromobacter Species1

Abstract: Volatile compounds produced by Pseudomonas putrefaciens, P. fluorescens, and an Achromobacter species in sterile fish muscle (Sebastes melanops) were identified by combined gas-liquid chromatography and mass spectrometry. Compounds produced by P. putrefaciens included methyl mercaptan, dimethyl disulfide, dimethyl trisulfide, 3-methyl-i-butanol, and trimethylamine. With the exception of dimethyl trisulfide, the same compounds were produced by an Achromobacter species. Methyl mercaptan and dimethyl disulfide we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…The amines were all found beginning in the second week of sampling, but were produced in the highest concentrations during the third week. In previous studies, trimethylamine has been identified as a bacterial metabolite (Miller et al, 1973;Rivers et al, 1992), but to our knowledge none of the amines detected here have been found as bacterial metabolites. No amines were emitted from the cultures growing on the building materials.…”
Section: Resultsmentioning
confidence: 42%
“…The amines were all found beginning in the second week of sampling, but were produced in the highest concentrations during the third week. In previous studies, trimethylamine has been identified as a bacterial metabolite (Miller et al, 1973;Rivers et al, 1992), but to our knowledge none of the amines detected here have been found as bacterial metabolites. No amines were emitted from the cultures growing on the building materials.…”
Section: Resultsmentioning
confidence: 42%
“…Slightly higher H 2 S sensor values were also noticed in the superchilled groups E and F, which can be explained by dominance of the H 2 S-producers in these groups (25% and 36%, respectively) (Table 1). At advanced spoilage of whole fish on ice, onion-like, sulfide and rotten vegetable-like, putrid spoilage odors develop because of microbially produced sulfur compounds (Shewan and others 1953;Miller 1973a;Herbert and others 1975). Earlier studies using the FreshSense electronic nose have shown increasing response of H 2 S and SO 2 sensors at advanced spoilage of whole capelin and redfish others 2000, 2002), but response to fillets of cod and haddock is generally much lower (Tryggvadóttir and others 2001).…”
Section: Tvb-n Analysis Tvb-n Analysis Tvb-n Analysis Tvb-n Analysis mentioning
confidence: 99%
“…Methanethiol is a metabolite of both Pseudomonas and Achromobacter spp. (Miller et al, 1973a), while formaldehyde is formed by microbial oxidation of trimethylamine by marine Pseudomonas spp. (Hebard et al, 1982).…”
Section: Crustaceansmentioning
confidence: 99%